Preparation of ZnO Nanorods Films by Electrodeposition Method - Wu, Shi-Biao; Xu, Ling; Xu, Hai-Yan; Li, Fei-Fei; Ge, Ye-Jun; Yao, Wei; Xu, Pan (Asian Journal of Chemistry, 2014)
Zinc oxide nanorods films were electrodeposited on indium tin oxide glass from aqueous solution by potentiostatic method. The XRD patterns indicate the films are polycrystalline with obvious (002) preferred crystal orientations. SEM morphology proves the ZnO nanorods’ growth of c axis (002) preferred orientations. The optimal preparation conditions were followings: deposition time, temperature and deposition potential were 1 h, 80 ºC and -1.0V (vs. SCE), respectively; Plating electrolyte contained 0.05 mol/L Zn(NO3)2, 0.1 mol/L hexamethylenetetramine and polyethylene glycol 400 (PEG 400); the volume ratio of PEG400 dosage and final plating electrolyte was 5 % in terms of percentage.